Applications of biotechnology and genomics in potato improvement. Issue 8 (7th August 2013) - Barrell, Philippa J.; Meiyalaghan, Sathiyamoorthy; Jacobs, Jeanne M.E.; Conner, Anthony J.
Summary: Potato is the third most important global food crop and the most widely grown noncereal crop. As a species highly amenable to cell culture, it has a long history of biotechnology applications for crop improvement. This review begins with a historical perspective on potato improvement using biotechnology encompassing pathogen elimination, wide hybridization, ploidy manipulation and applications of cell culture. We describe the past developments and new approaches for gene transfer to potato. Transformation is highly effective for adding single genes to existing elite potato clones with no, or minimal, disturbances to their genetic background and represents the only effective way to produce isogenic lines of specific genotypes/cultivars. This is virtually impossible via traditional breeding as, due to the high heterozygosity in the tetraploid potato genome, the genetic integrity of potato clones is lost upon sexual reproduction as a result of allele segregation. These genetic attributes have also provided challenges for the development of genetic maps and applications of molecular markers and genomics in potato breeding. Various molecular approaches used to characterize loci, (candidate) genes and alleles in potato, and associating phenotype with genotype are also described. The recent determination of the potato genome sequence has presented new opportunities for genomewide assays to provide tools for gene discovery and enabling the development of robustly unique marker haplotypes spanning QTL regions. The latter will be useful in introgression breeding and whole‐genome approaches such as genomic selection to improve the efficiency of selecting elite clones and enhancing genetic gain over time.